PERAN TEKNOLOGI DALAM PEMBELAJARAN KURIKULUM MERDEKA DI SDN 06 BELANTIK - Muhammad Farid; Mutiara Putri; Raissa Rahmah; M. Jaya Adi Putra; Mauliatun Nisa (CV. ADIBA AISHA AMIRA, 2024)
The implementation of the Merdeka Curriculum in elementary schools requires significant changes in teaching methods, one of which is the integration of technology. This article aims to analyze the role of technology in supporting the learning process in the Merdeka Curriculum, particularly in terms of assessment, collaboration, and the development of 21st-century skills. This research analyzes the role of technology in the learning of the Merdeka Curriculum conducted at SDN 06 Belantik, Siak Regency. Using descriptive methods and a qualitative approach, data were collected through the completion of questionnaires by 3 (three) teachers via Googleform. Research results show that technology plays an important role in supporting the implementation of the Merdeka Curriculum by facilitating the learning process, conducting formative assessments, and increasing student engagement. However, despite that, challenges such as limited infrastructure, teacher capabilities, and internet access become significant obstacles. Students' acceptance of technology is also positive, increasing their interest and engagement in learning. Thus, continuous training, improvement of technological facilities to support effective learning in the digital era, as well as the utilization of available digital devices and cloud-based applications to address existing challenges, are necessary to achieve educational goals in line with the Pancasila Student Profile.